2015
DOI: 10.1089/scd.2014.0439
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Surface Antigen (MA6) by Peripheral Blood CD34+Cells Is Correlated with Improved Platelet Engraftment and May Explain Delayed Platelet Engraftment Following Cord Blood Transplantation

Abstract: CD34 + cell dose provides a measure of hematopoietic tissue that predicts the rate of engraftment upon transplant. It is positively correlated with multiple measures of hematopoietic recovery, including platelet engraftment. Here we identify a subpopulation of CD34 + cells that coexpress a surface antigen-MA6, which is more positively correlated with platelet engraftment in a clinical setting than CD34 + alone. The specific identity and function of MA6 remain to be determined, however, it is expressed by primi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Our results revealed that the treatment had no significant effect on the percentage of CD34-expressing cells suggesting that the treatment preserves the CD34+ phenotype of HSPC, an important index of hematopoietic recovery. 19 However, treatment also showed a significant increase in the CD34 MFI which was likely the result of cell enlargement that occurs during the S phase of the cell cycle as shown in Figure 1C. Furthermore, evaluation of the clonogenic ability of primed CD34+ cells using the MethoCult assay, indicated that our treatment did not negatively affect the clonogenic capacity of HSPC, thus supporting the potential use of this approach on this latter cell type.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Our results revealed that the treatment had no significant effect on the percentage of CD34-expressing cells suggesting that the treatment preserves the CD34+ phenotype of HSPC, an important index of hematopoietic recovery. 19 However, treatment also showed a significant increase in the CD34 MFI which was likely the result of cell enlargement that occurs during the S phase of the cell cycle as shown in Figure 1C. Furthermore, evaluation of the clonogenic ability of primed CD34+ cells using the MethoCult assay, indicated that our treatment did not negatively affect the clonogenic capacity of HSPC, thus supporting the potential use of this approach on this latter cell type.…”
Section: Discussionsupporting
confidence: 52%
“…It is positively correlated with multiple measures of hematopoietic recovery, including platelet engraftment. 19 Our results show that a 24-hour exposure of HSPC to increasing concentrations of either hPL or cytokines, or to hPL combined with cytokines (hPL + cytokines), does not affect the number of cells expressing CD34 ( Figure 1A). However, we found a significantly increased mean fluorescence intensity (MFI) of CD34, which represents the density of the antigen expression on the cell surface, on cells primed with 36 mg/mL of hPL + cytokines (>3-fold; Figure 1B), compared to cells primed with either hPL or cytokines alone, or to untreated cells.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Many investigators worldwide are trying to achieve this goal but with limited success. [36][37][38][39][40] This is because the process of megakaryocyte and platelet formation is very complex and the mechanism is not yet completely understood. Two main approaches for in vitro MK production are genetic manipulations or altering media components.…”
Section: Discussionmentioning
confidence: 99%
“…Migliaccio et al ( 11 ) have compared TNC with colony-forming unit (CFU) numbers and have shown TNC to be inferior to CFU in determining neutrophil and platelet recovery speed following UCBT. Recently, Simmons et al have identified a CD34 + cell subpopulation that co-expresses an antigen (-MA6) ( 12 ). This antigen expression predicted platelet engraftment better than CD34 + cell counts.…”
Section: Predictors Of Engraftmentmentioning
confidence: 99%